And then there were eight : poems about space - Salas, Laura Purdie (A+ books. Poetry., 2008)
"A collection of original, outer space-themed poetry for children accompanied by striking photos. The book demonstrates a variety of common poetic forms and defines poetic devices"--Provided by publisher.